Leaf micro-morphological characteristics of selected Vatica species (Dipterocarpaceae) from Kubah National Park, Sarawak - Meekiong, K.; Latiff, A.; Tawan, C.S.; Miraadila, M.I. (Penerbit Universiti Kebangsaan Malaysia, 2012)
Genus Vatica L. is one of the largest groups in the family Dipterocarpaceae with 71 species have been botanically described, distributed from India, Sri Lanka to Myanmar, Indochina, Sumatra, Borneo and the Philippines. Borneo with 35 species has the largest representative. In Sarawak, 32 species have been recorded, occurring especially in mixed and upper dipterocarp forests and also non-saline habitats from sea level up to about 1,800 m altitude. Kubah National Park is among the richest site for genus Vatica in Sarawak with 11 species recorded. The Vatica species are distinguished from other genera of Dipterocarpaceae by the absence of looped intra-marginal nerves on leaf, winged fruits encloses less than half of the nut, glabrous anthers and stout style. However, in term of inter species within its genus, Vatica is the most difficult dipterocarp to be identified, which explains why this common genus so poorly known. This study was conducted to examine leaves characteristics particularly its micro morphology to differentiate some selected Vatica species from Kubah National Park. Leaves samples were observed via Scanning Electronic Microscope (SEM). The characteristics and indumentums were compared between each species and noted. Results show that leaf micro morphology characteristics are significantly useful to differentiate the species level and intra-specific level.